Futurescaping: school choice of internationally mobile global middle class families temporarily residing in Malaysia. Issue 5 (3rd September 2019) - Adams, Megan; Agbenyega, Joseph
ABSTRACT: This paper explores internationally mobile global middle class families (GMCF) in terms of how they rationalise moving away from their home country, select schools and reimagine their young children's futures in an international setting. Building on Appadurai's notion of 'the future as a cultural fact' and Anagnost's concept of 'life-making in neoliberal times' we analyse how the search for escaping the past is dialectically related to seeking better futures. For GMCFs, the search for better futures within current neoliberal times leads to them discursively constructing spatial–temporal movements across international boundaries. The term 'futurescaping' is introduced and used to understand the act of imagining futures that are shaped by a person's past and present experience. We argue that futurescaping is more than simply transnational mobility, but is a multidimensional act, which is dynamic, culturally value-ladened, historically embedded, futuristic and provides a unique view into the everyday lives of internationally mobile GMCF.